E-Learning in Institute of Higher Education in Malaysia - Joseph Thomas, J.Soosiamaal A/P; Annadurai, Priyadiana (Journal of ICT in Education, 2021)
This paper review to focus the relationship between Generation Y students and Malaysian cultural factors within the context of an e-learning application. E-learning is defined as the use of electronic media in learning. Meanwhile, Generation Y is defined by the internet and is a connected global generation. The results of these studies on Generation Y culture may differ from those obtained from research focusing on Generation Y and cultural nuances separately. Hofstede’s multicultural model is used in this study to better understand the unique cultural nuances of Malaysian Generation Y students. Every dimension of Hofstede’s cultural model has been adapted to the context of e-learning in Malaysia. This review also explores whether both Generation Y and culture influence the student usage of e-learning education. This model can be utilized as a guide for e-learning developers to create an appropriate pedagogy for Generation Y students in higher educational institutes in Malaysia.